P0505COST ANALYSIS OF SCREENING FOR IGA NEPHROPATHY USING NOVEL BIOMARKERS. (6th June 2020) - Ishida, Mami; Matsuzaki, Keiichi; Ikai, Hiroshi; Suzuki, Hitoshi; Suzuki, Yusuke
Abstract: Background and Aims: IgA nephropathy (IgAN) is the most common primary chronic glomerulonephritis and a major cause of end-stage kidney disease worldwide. Recently, novel biomarkers including aberrantly glycosylated IgA1 and the glycan-specific antibodies can be measured and will predict the IgAN. However, little is known about the cost-effectiveness of this screening method from the societal perspective. This is the cost analysis of additional novel biomarkers to the conventional IgAN screening strategy. Method: Cost analysis was carried out to compare the two diagnostic strategies with or without biomarkers. We developed an analytical decision model to estimate the lifetime medical expense of each strategy. The decision tree was started at forty years old with first time hematuria, and simulated the clinical strategy after the screening using the novel biomarkers (Group N: N), and conventional strategy (Group C: C). The result of the analysis is presented as the lifetime medical expenses from societal perspective. Discount was not considered. Results: Lifetime medical expenses per person during forty years were calculated as 31.6 million JPY (≈287, 270 USD) for using the novel biomarkers, 33.9 million JPY (≈307, 903 USD) for conventional strategy. They were lower by 2.3 million JPY (≈20, 633 USD) in Group N. Moreover, by using the novel biomarkers, the expected value of IgAN led to increase by 5.67 percent points (N: 48.44%, C: 42.77%), and the expected value of the dialysis led to decrease by 0.85 percent points (N: 19.91%, C: 19.06%). One-way sensitive analysis showed that the prevalence of IgAN was the most influential variable. In the sensitivity analysis, the rate of tonsillectomy with steroid pulse therapy and achieved clinical remission was higher, the expected lifetime expenses were reduced by 3.3 million JPY (≈30, 355 USD) and the expected value of the dialysis led to decrease by 1.76 percent points (N: 11.80%, C: 13.56%). Conclusion: Screening for IgAN using novel biomarkers is expected to reduce the lifetime medical expenses.